Gender neutrality and the Prevention and Treatment of Violence – A Dutch Perspective - Althoff, Martina (Women & criminal justice, 2021)
One of the important themes in debating violence in the international political fora is ‘violence against women’, which is explicitly emphasized by The Convention of Istanbul. The Netherlands have ratified this convention but partially due to Dutch influence it was stated that although women do suffer more from violence, that does not mean that there are no male victims of violence and that the state and policy makers should provide for them too. As a consequence, Dutch government aims at ‘gender neutrality’ in their approaches to prevent and treat violence. This approach has dealt with some criticism, some wonder nowadays whether this focus on ‘gender neutrality’ has negative consequences for addressing the hardship that women have to deal with. In our contribution we will try to answer the previous question by looking into three examples: domestic violence, honour-related violence, and prostitution & human trafficking policy, all in the Netherlands.